Analisis Dampak Ekonomi Implementasi Kebijakan Revitalisasi Pasar Tradisional (Studi Kasus pada Revitalisasi Pasar Tanggul Surakarta - Tifani Sasnila Silitonga; Asal Wahyuni Erlin Mulyadi (Jurnal Mahasiswa Wacana Publik, 2021)
This research discuss about economic impact of market implementation revitalization in Pasar Tanggul Surakarta. Pasar Tanggul is a traditional market that has more value because Pasar Tanggul is the only one traditional market in Surakarta with Indonesian National Standard certificate and disabled friendly market. Purpose of this research is to evaluate implementation of revalization through economic impact analysis with Stynes indicators, namely sales, market trader income, employment. Another purpose is to determine factors that influence implementation of Pasar Tanggul Revitalization. This research is qualitative research with study case approach. Data collection methods is interview, observation, documentation. Data are processed by interactive analysis. The results show the economic impacts after revitalization are sales volume and market traders income have decreased, labor absorption in Pasar Tanggul has increased. Implementation of Pasar Tanggul revitalization is influenced by several factors like communication, resource, disposition, and bureaucratic structure which is good and suffice. The problem of Pasar Tanggul Revitalization is there was a protest from people who asked for stalls because they used to build a buildings around market. Some traders refused revitalization because they are worried that their merchandise will not sell, but these problem can be solved through a good approach and communication.